Torcedores antifascistas de futebol: táticas comunicacionais de resistência às normatizações na cultura futebolística - Soares, Alison Rodrigues (Universidade do Vale do Rio dos Sinos, 2022)
The intent of this dissertation was to observe the communication tactics formulated by anti-fascist supporters - ASs -, from the city of Porto Alegre, Grêmio and Internacional supporters. The research mapped the communication actions made in the social media Instagram, as well as other forms of online communication. By this means, it was possible to perceive how the online presence it's able to complement the activism actions taken in everyday life, along with its tactics of interpersonal communication. For this approach, a transmethodological epistemology was used (MALDONADO, 2015), which the empirical was complexified through exploratory methodologies (BARDIN, 1977; BONIN, 2013; MILLS, 2009); methodological research (BONIN, 2013); along with an adaptation of participant observation methods (PERUZZO, 2003) called in this dissertation “observation-participatory-research”. From this study, it was possible to notice how the interpersonal communicational contact is irreplaceable in a goal of change of reality and/or pedagogy. For the anti-fascist tactics of the ASs, online platforms are important because they have a relevant pedagogical role - but it is essential to be physically present in the coexistence of those who can be co-opted by the praxis of neo-fascist hatred. In the specificity of sport, it’s necessary to be present at stadiums and in the various environments of the city that promote meetings of supporters. In the pedagogy proposed by the ASs, it was possible to perceive similarities to the Freirean pedagogy of the oppressed (FREIRE, 2020), which through its tactics reveals to be possible to succeed in the knowledge of generating themes that affect football fans in general - in particular those oppressed by the white norm, male, heterosexual, cisgender and aporphobic (ALMEIDA, 2020; BUTLER, 2018; FOUCAULT, 1988; CORTINA, 2020).

La intención de esta disertación fue observar las tácticas de comunicación formuladas por los hinchas antifascistas - HAs -, de la ciudad de Porto Alegre, y sus de Grêmio y Internacional. La investigación mapeó las acciones de comunicación realizadas en la red social Instagram, así como otras formas de comunicación en línea. De esta manera, fue posible percibir cómo la presencia en línea es capaz de complementar las acciones de activismo realizadas en la vida cotidiana, junto con sus tácticas de comunicación interpersonal. Para este abordaje se utilizó la epistemología transmetodológica (MALDONADO, 2015), cuya empírica fue complejizada a través de metodologías exploratorias (BARDIN, 1977; BONIN, 2013; MILLS, 2009); investigación metodológica (BONIN, 2013); junto con una adaptación de métodos de observación participante (PERUZZO, 2003) denominada en esta disertación “investigación-observactiva-participativa”. A partir de este estudio, fue posible percibir cómo el contacto comunicacional interpersonal es insustituible en un objetivo de cambio de la realidad y/o de la pedagogía. Para la táctica antifascista de las HAs, las plataformas en línea son importantes porque tienen un papel pedagógico relevante, pero es fundamental estar físicamente presente en la convivencia de quienes pueden ser cooptados por la praxis del odio neofascista. En la especificidad del deporte, es necesario estar presente en los estadios y en los diferentes ambientes de la ciudad que promuevan encuentros de aficionados. En la pedagogía propuesta por los HAs fue posible percibir similitudes con la pedagogía freireana del oprimido (FREIRE, 2020), que a través de su táctica revela que es posible lograr el conocimiento de temas generadores que afectan a los hinchas de fútbol en general. - en particular los oprimidos por la norma blanca, masculina, heterosexual, cisgénero y aporofobica (ALMEIDA, 2020; BUTLER, 2018; FOUCAULT, 1988; CORTINA, 2020).
Keywords: Torcedores; Futebol; Táticas comunicacionais; Cultura futebolística; Fans; Football; Communication tactics; Football culture; Aficionados; Fútbol americano; Tácticas de comunicación; Cultura del fútbol; ACCNPQ::Ciências Sociais Aplicadas::Comunicação